Peran Komunikasi Interpersonal Dalam Pola Asuh Anak di Media Tiktok @thehartono'sfamily - Arneta Meitereza; Ratnaningrum Zusyana Dewi (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2025)
Open communication involves sharing information, feelings, and thoughts honestly and transparently. The role of parents in family interactions is explored in this study, focusing on the @thehartono'sfamily TikTok account's impact on children's character formation. Using qualitative descriptive analysis, the research examines content from the @thehartono'sfamily TikTok account, revealing three main aspects. Firstly, the learning of values and ethics. Secondly, the modeling of positive parental behavior in interactions. Lastly, the provision of support and guidance. Videos on the @The Hartono's Family TikTok account from July 2022 to December 2022 illustrate the parental role in open communication and its influence on children's character development. This family serves as an example of how positive character traits and integrity can be cultivated through open communication. The study suggests, as shown by the @thehartono'sfamily TikTok account, that through open communication, children can achieve their full potential in developing positive character.